THE REALITY OF SOVEREIGN DEBT AND THE POSSIBILITIES OF ADDRESSING IT THROUGH FISCAL AND MONETARY POLICY MEASURES IN THE ENVIRONMENT OF THE IRAQI ECONOMY - Hayat Jumaah Mohammed (American Journals, 2023)
Despite the availability of natural and other resources in the environment of the Iraqi economy, the increase and exacerbation of sovereign debt owed by Iraqi governments cause a major problem in the environment of the Iraqi economy. However, any country that enjoys abundant resources with this huge amount of diversity between agricultural, industrial, natural, tourism, and advanced human resources cannot be expected to avoid incurring sovereign debt. It is shackled by the restrictions of external debt, particularly sovereign ones. Hence, the research aims to show the importance and extent of the seriousness of sovereign debt and its repercussions on the economic sectors in any country. This is because sovereign debt significantly affects the growth of the productive sectors through the inability of those sectors to increase production. The reason for this is that it is well known to everyone. Sovereign debt is the accumulation of debt that is owed to a nation's government by its citizens. Because these debts weigh down the economy, it is impossible to increase production because all or the majority of the available revenues go to pay off those debts and the interest that accrues on them and has to be paid. Then there is no money left over to pay for anything else. It is necessary that every production process be funded either internally or externally for the production process to continue indefinitely. Providing evidence that the steps taken by decision-makers can adopt financial and monetary policies that would either prevent these debts or achieve the required balance in a way that does not impede the forward movement of development processes within the sector is an important step. Increasing both the level of productivity in these areas and the amount of cash made available to support it is a priority.Moreover, without burdening the economy with debts that serve no purpose in expanding these areas of the economy. In addition, a negative interaction effect begins to show up after the year 2003 through the use of two indicators with a theoretical basis. The first one is exemplified by (inconsistency in time), particularly by deviating from its primary objective (maintaining stability in the general level of prices) at the expense of providing a cover for the budget deficit and public debt through the currency window, which generates a huge cash block in economic activity while not depleting foreign reserves in the environment of the Iraqi economy. One of the most important recommendations is maintaining consistency between fiscal and monetary policies when faking inflation. The trend is heading in the wrong direction.
Keywords: Sovereign debt, fiscal policy, monetary policy.